Green synthesis and characterization of copper(II) oxide nanoparticles derived from lemon peel extract for the photocatalytic degradation of palm oil mill effluent (POME) - Tan, Lee Xian (2022)
The properties of matter at nanoscale are significantly different from their macroscopic bulk properties. Metal nanoparticles have been applied for various applications, such as biosensor, controlled drug delivery, antimicrobial agent and photocatalysts for wastewater treatment. Nanoparticles able to degrade pollutants under ultraviolet (UV) light, is one the favorable method for wastewater treatment. Nowadays, there are various physical and chemical methods have been used to synthesize nanoparticles. However, there are a lot of serious threats to the environment by using these methods due to the usage of toxic chemicals and solvents, consumption of high energy, high cost, and tedious procedure. Therefore, there is a need for “green synthesis” of nanoparticles due to its simplicity, nontoxicity, nonexpensive, energy efficiency, and environmentally friendliness. In this study, copper(II) oxide nanoparticles, CuO NPs were synthesized using lemon (Citrus limon) peel extract (LPE) as reducing and stabilizing agent, and copper(II) nitrate trihydrate salt as precursor. LPE was prepared with deionized water by heating 20 minutes and filtering twice, and copper(II) nitrate trihydrate was added into LPE with continuous heating and stirring until dark green paste is obtained. Then, dark green paste was calcinated in furnace at 450 °C for 2 hours. Green synthesized CuO NPs were characterized by UV-visible (UV-vis) spectroscopy, fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The photocatalytic activity of the CuO NPs was evaluated by degradation of palm oil mill effluent (POME) under UV irradiation, and the extend of POME degradation was observed by measuring chemical oxygen demand (COD) values. The results showed 81 % of the POME was successfully degraded under UV irradiation for 3 hours. The phytotoxicity experiment using mung bean (Vigna radiata L.) seed also showed a decreasing in toxicity of POME after photodegradation.